دور تكنولوجيا المعلومات في تحسين إدارة الموارد البشرية في مصحة الفارابي ( دراسة ميدانية في مصحة الفارابي) - باسي, الهام (Sciences de l'Homme et de la Société, 2013)
إن الدور الفعال الذي تمارسه تكنولوجيا المعلومات في بيئة الأعمال، جعل منها مركز اهتمام المؤسسات و أساس تنافسها.  تأتي  هذه الدراسة بغية تبين دور تكنولوجيا المعلومات في تحسين إدارة الموارد البشرية في مصحة الفارابي، وقد تم الاعتماد على تحليل نتائج الاستبيان لتحديد العلاقة و الخروج بتوصيات، بعد تحليل نظري حول الموضوع.   The effective role played by information technology in the business environment, makes it  the center of attention of institutions and the  basis of their competition. This study comes in order to show the role of information technology in improving the management of human resources in the Farabi sanatorium: we relied on the analysis of the questionnaire results to determine the relationship and come up with recommendations, after a theoretical analysis on the topic.